2022
DOI: 10.3390/jcm11030647
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Consumption in Chronic Pain Patients: Role of Perceived Injustice and Other Psychological and Socioeconomic Factors

Abstract: Background: Chronic pain is a complex biopsychosocial phenomenon. Lifestyle, behavioral, socioeconomic, and psychosocial factors such as depression and perceived injustice are often associated with the development of chronic pain and vice versa. We sought to examine the interaction of these factors with opioid intake. Methods: At our institution, 164 patients with chronic pain undergoing an interdisciplinary assessment within a three-month period participated in the study and completed the Injustice Experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In the elderly population (i.e., > 65 years of age), problematic opioid use and OUD have been increasingly observed, with both illicit and prescription opioids [45]. Risk factors for OUD development in this patient cohort include multimorbidity, long-term alcohol misuse, depression, or chronic pain disorder [45,46]. Along with the current therapy plans established from the data of younger adults, elderly patients respond well to opioid agonist therapy, while age is no obstacle to treatment [45].…”
Section: Risk Factors In Pediatric Adolescent and Elderly Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the elderly population (i.e., > 65 years of age), problematic opioid use and OUD have been increasingly observed, with both illicit and prescription opioids [45]. Risk factors for OUD development in this patient cohort include multimorbidity, long-term alcohol misuse, depression, or chronic pain disorder [45,46]. Along with the current therapy plans established from the data of younger adults, elderly patients respond well to opioid agonist therapy, while age is no obstacle to treatment [45].…”
Section: Risk Factors In Pediatric Adolescent and Elderly Patientsmentioning
confidence: 99%
“…Regardless of age, however, opioid misusage has been linked to psychological factors and single social determinants of pain rather than somatic factors [46].…”
Section: Risk Factors In Pediatric Adolescent and Elderly Patientsmentioning
confidence: 99%
“…One important study reports that graded exposure in vivo treatment in patients with chronic low back pain and complex regional pain syndrome type I was accompanied by reductions in fear that preceded pain relief [ 5 ]. Another original study reported that opioid use was more closely related to perceived injustice and depression, but not anxiety and stress in 164 patients with chronic pain [ 6 ]. In a study of patients post COVID-19 infection ( n = 567), more than 70% presented symptoms of central sensitisation [ 7 ].…”
Section: State Of the Art Papers And Original Contributionsmentioning
confidence: 99%